Let's cook about it! - Waweru, Carol; Machogu, Diana; Eyase, Jean; Kramer, Berber; Kvuva, Benjamin (International Food Policy Research Institute, 2023)
Many nations in Africa South of the Sahara rely on agriculture for their livelihoods and their food security is threatened by climate change. Kenya, which has been experiencing an increased frequency of drought events - with the most recent drought (2020-2023) being the worst drought in four decades - is no exception. Given this increased frequency of extreme weather events, it is important that farmers use climate adaptative practices in their farming, such as the use of drought tolerant seeds. Although great strides have been made in breeding earlier maturing drought-tolerant varieties, a majority of farmers continue to grow older varieties. For instance, one of the common maize varieties grown in Kenya was released more than 30 years ago and the average varietal age continues to increase over time (Rutsaert & Donovan, 2020; De Groote & Omondi, 2023).